The Influence Of PayLater, Live Streaming Shopping, And Flash Sale On Impulsive Buying Behaviour Among Generation Z Shopee Users - Vitari Hana Saputri; Irwan Susanto; Maliana Puspa Arum (UNIVED Press, 2026)
This study explores the impacts of PayLater, Live Streaming Shopping, and Flash Sale features on impulsive buying behaviour among Generation Z Shopee users. This research adopts a quantitative approach, collecting data via an online questionnaire administered to 100 respondents chosen through purposive sampling. Data analysis was carried out using multiple linear regression in SPSS version 29 to determine both partial and simultaneous effects of the variables. The results showed that PayLater, Live Streaming Shopping, and Flash Sale each demonstrated a positive and significant impact on impulsive buying behaviour. Taken together, the three features demonstrated a statistically significant, positive effect on impulsive buying behaviour. An R² of 0.814 suggests that PayLater, Live Streaming Shopping, and Flash Sale explain 81.4% of the variation in impulsive buying behaviour, which is classified as a strong influence. The research model explains most of the variation in impulsive buying behaviour, indicating that marketing strategies based on ease of payment, real-time interaction, and time urgency effectively influence Generation Z's purchasing decisions.